State and risk production: a case study from river communities in Belen-Iquitos - Gorenstein, Sharon (2019)
Developmental policies, or development projects in general, have consistently failed to achieve their stated objectives by being based on a «construction» of the country/community/space that bears little relation to local culture. While development projects fail, the government succeeds in expanding the field of bureaucratic state power in the space that needs to be «developed». Seen from a notion of governmentality, socially legitimated authorities interfere in spaces isolated from the actual development by focusing on adjudicating the vices or virtues of developmental policies and their risks or lack thereof. In this way, risk works as a calculative rationally associated with welfare as a way of representing events, such as flooding, so they can be made governable. By focusing on the contrast between the risk perceptions of the state and river communities in the district of Belen, I attempt to contribute to recent debates about government risk assessment as the reorganization and simplification of natureto suit developers’ and public and private institutions’ goals. I analyze and identify three differentdimensions of risk understanding: view of the river; notions of development; and belenino identity.